CAGAITA A STUDY USING THE RESPONSE METHODOLOGY TO DEFINE THE BEST EXTRACTION PARAMETERS - Silva, Jaqueline Ferreira; Rossoni, Diogo Francisco; Alves, Tayane Siqueira Garcia; da Silva, Luciana Alves; da Silva, Larissa Rodrigues; de Souza, Isabela Milani; dos Santos Picanço, Gabrielle; Schipfer, Caroline Wolf Trentini; Stafussa, Ana Paula; Marques, Amábile Mariano; Guedes, Carmen Torres; da Silva Scapim, Mônica Regina (Seven Editora, 2025)
The Brazilian Cerrado is a biome with great territorial extension and consequently numerous native fruits that have a great technological potential, mainly due to its nutritional composition and bioactive compounds. Thus, this work aims to use the response surface methodology for optimization in the process of extraction of bioactive compounds for Cagaita fruit. The extraction temperature (60 °C) and the solvent (water) used were those that presented the greatest emphasis for optimization in the extraction of bioactive compounds. This result allows subsequent developments by characterizing the extract more widely, application of other technologies such as evaporation, microencapsulation and nanoemulsion, promoting greater technological development and a greater knowledge about the fruit by the population and the different regions.DOI:  https://doi.org/10.56238/sevened2025.026-032